Patterns of recurrence after prostate bed radiotherapy. (December 2019) - Brand, Douglas H.; Parker, Joanna I.; Dearnaley, David P.; Eeles, Rosalind; Huddart, Robert; Khoo, Vincent; Murray, Julia; Suh, Yae-Eun; Tree, Alison C.; van As, Nicholas; Parker, Chris
Highlights: Pelvic nodal recurrence was common after salvage radiotherapy to prostate bed. Pelvic nodal disease was often the only site of recurrence. Pelvic nodal recurrence was not associated with pre-treatment PSA. There is a case for including pelvic nodes as well as prostate bed in treatment volume. Abstract: Background and purpose: Prostate bed radiotherapy is a standard treatment after radical prostatectomy. Recent evidence suggests that, for patients with a PSA > 0.34 ng/ml, the radiotherapy treatment volume should include not only the prostate bed but also the pelvic lymph nodes. We describe the patterns of failure after prostate bed radiotherapy, focussing on the proportion of patients with radiologically confirmed pelvic nodal failure only, in the absence of distant disease. Materials and methods: Patients included were men receiving prostate bed radiotherapy at the Royal Marsden Hospital between 1997 and 2013. The key outcome of interest was the pattern of radiologic failure after prostate bed radiotherapy. Baseline characteristics of patients experiencing pelvic nodal failure without distant disease were compared versus all other relapse patterns. Comparisons were by Chi-square test, with multiple testing adjusted p  < 0.005 significant. Results: 140 of 322 patients developed biochemical failure after salvage RT. Radiologic failure occurred in 89 patients. 35 of the 89 patients (39%) with radiologic failure had pelvic nodal failure without distant disease, with no significant differences in baseline characteristics when compared to all other patients. The rate of pelvic nodal failure was the same for patients with PSA above or below 0.34 ng/ml (16/149, 95% CI = 6–17% vs 19/171, 95% CI = 7–17%). Conclusions: Pelvic lymph node disease, without more distant disease, is a common site of failure in men receiving radiotherapy to the prostate bed, including those with PSA < 0.34 ng/ml. This observation informs the case for including the pelvic lymph nodes in the radiotherapy treatment volume.